Rethinking Legal Status of Polytechnic in the Law of Education System - Tonny Pongoh; Henry Soelistyo Budi; Bintan R. Saragih (Universitas Pelita Harapan, 2021)
The legal status of polytechnic has been fundamentally changed from time to time. After the Law of National Education System Number 20/2003 and the Law of Higher Education Number 12/2012 came into effect, the polytechnic has been granted a new legal status that offers more diverse programs at various levels. Since then, polytechnic could conduct vocational diploma programs and degree programs in applied sciences from graduate to postgraduate. This legal status raises legal problems whether polytechnic is a higher education institution in vocational or applied sciences. Best education practices in some countries classify applied sciences higher education as academic education, not vocational education. This doctrinal research paper then will examine this legal problem using statute, historical and comparative approach, in the light of the Development Legal Theory. This study shows that the legal status of polytechnic is heavily dependent on government policy. In the absence of a clear and firm ground policy of vocational education, the legal status of the polytechnic has been interpreted differently from time to time. The government ought to reset the vocational education policy and then reform the law of the national education system. Therefore, the legal status of the polytechnic will be more sustainable and have better legal certainty accordingly. Regarding the recent development of higher education, it will be better if the government constitutes polytechnic as a higher education institution in applied sciences.